PENGGUNAAN INTERNET SEBAGAI MEDIA SUMBER LITERATUR OLEH MAHASISWA AKUNTANSI (Studi Kasus Pada Mahasiswa Program Studi S1 Akuntansi Universitas Semarang) - Widowati, Amerti Irvin; Surjawati, Linda Ayu Oktoriza (Jurnal Dinamika Sosial Budaya, 2018)
The purpose of this study is to determine the determinants of the use of the Internet as a medium of literature sources by students of master programs. Data were collected from 300 students of Accounting Program of Semarang University by survey method. Data were analyzed using Partial Least Square (PLS) application. The results of this study indicate that the perception of ease, perception of internet content, and the personality of openness have a significant positive influence on internet usage. While the perception of usability has no significant effect on internet usage. The result of this research can have implication to the lecturer as well as the decision maker about the perception of the student about the internet usage as the literature source. In addition the lecturers can describe the behavior of students who have a tendency to use the internet.
Keywords: perception of usability; perception of ease of use; perception of internet content; personality of openness; internet usage; media source literature.